Velocity of Money Income and Economic Growth in Sudan: Cointegration and Error Correction Analysis - Mohamed, Elwasila Saeed Elamin (International Journal of Economics and Financial Issues, 2020)
This study explores the linkages between velocity of money and economic growth in Sudan using conitegration and error correction methods in the context of the quantity theory of money QTM without inclusion of institutional factors. Cointegration analysis confirms existence of a long run equilibrium relationship between velocity of money and economic growth. The empirical analysis shows that velocity of money is significantly and positively affected by GDP and broad money, validating the QTM. Velocity of money is also found to be positively affected by trade openness, government deficit but negatively affected by inflation and investment. Granger causality test shows unidirectional relationships running from GDP, inflation and financial development to velocity of money. A bidirectional causality between velocity and trade openness is detected. These findings suggest that velocity of money is driven mostly by expansionary monetary policy and monetization of government deficit, which should be controlled. Keywords: Velocity of money; GDP; Inflation; Financial development; unemployment; trade openness JEL Classifications: C32, E10, E40, E63 DOI: https://doi.org/10.32479/ijefi.8944